The Influence of Work Experience, Teamwork, and Creativity on Employee Performance at PT Karya Kreasi Madani - Alweni, Alweni; Sukarno, Gendut; Santoso, Bowo (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to explore the influence of work experience, teamwork, and creativity on employee performance at PT Karya Kreasi Madani. In this case, work experience, teamwork, and creativity are considered important in improving employee performance. This research employs a quantitative approach by utilizing a questionnaire for data collection. The study's population consists of employees at PT Karya Kreasi Madani, with a sample size of 43 respondents. The data analysis was conducted using the Partial Least Square (PLS) method. The findings revealed that work experience positively and significantly impacts employee performance at PT Karya Kreasi Madani, as well as teamwork and creativity influence the employee performance of PT Karya Kreasi Madani. These findings indicate a relationship that mutually influences work experience, teamwork, creativity, and employee performance.